Automating the Conceptual Modeling of Data Warehouse in Information System ERP Type - Elotmani, Ayoub; Bouden, Pr. Halima (Transactions on Engineering and Computing Sciences, 2017)
An information system type ERP (enterpriseresources planning) aims to control the information flow and ensure the integrity of unique repository. However, the strategic level of thisorganization is looking to note a knowledge for vocation to decide and forecast. This feasible with the introduction of the business intelligence, which allowing storing historical data and organized in storage space: datawarehouse (DWH), reduced to data mart (DM) that are an extract of the DWH adopted to a specific use, it is modelled for OLAP (on line analytical processing) analyses. This article is part of a critical study, about the three Data Warehouse design approaches, in order to make the best approach adaptable to an ERP database. On the order hand, to study the proposals of the automation of the phases of the design of the warehouse.